Association between serum IgG level and clinical course in primary sclerosing cholangitis - Wenz, Theresa; Sauer, Peter; Goeppert, Benjamin; Schirmacher, Peter; Gotthardt, Daniel; Weiss, Karl Heinz; Stremmel, Wolfgang; Rupp, Christian (BMC gastroenterology, 2019)
Primary sclerosing cholangitis is a chronic cholestatic liver disease. The pathomechanism is still not fully understood, but there is evidence that immune-mediated processes may contribute to disease progression.
Gesehen am 07.11.2019